Utility of Hematology Histograms - Prabhat, Daksha; Waghmare, Tejaswini; Rangwala, Tasneem (Annals of Pathology and Laboratory Medicine, 2019)
Background: Over the past five decades, hematology analyzers have evolved from semi-automated to fully automated ones. A histogram is a graphic representationof a collection of data based on cell size and/or cell number depicting variations in the process. Objective: To study hematology histograms in relation with major blood cell components and in cases of acute febrile illness. Methods: It was a cross sectional observational study conducted over 200 consecutively collected samples from adults. Histograms were obtained from 3-part automated hematology analyzer, evaluated in relation to the RBCs, WBCs and platelets with their peripheral blood smear (PBS) picture and with the cases with diagnosis of acute febrile illness. Results: In the present study, maximum number of samples were from 15-25 years of age group with a male preponderance. Out of 200 histograms, 102 had combined abnormality of the all 3 blood cell types in varied combinations. Neutrophilia, microcytosis and thrombocytopenia were the most common findings in the respective individual blood cell histograms. Maximum sensitivity of WBC histogram was for neutrophilia (81.08%), that of RBC histogram was for microcytosis (81.3%) while that of platelet histogram was for thrombocytopenia (97.5%). In cases of acute febrile illness, dengue was the most common diagnosis with thrombocytopenia being most common histogram finding. Conclusion: Histograms provided by the automated hematology analyzers are of great diagnostic and morphologic importance. Histograms obtained from automated analyzers should be complementary to hematological parameters and peripheral blood smear examination.